Valuation study for a preference-based quality of life measure for dental caries (Dental Caries Utility Index - DCUI) among Australian adolescents - study protocol. Issue 10 (21st October 2020) - Hettiarachchi, Ruvini; Kularatna, Sanjeewa; Byrnes, Joshua; Mulhern, Brendan; Chen, Gang; Scuffham, Paul A
Abstract : Introduction: A new health state classification system has been developed for dental caries - Dental Caries Utility Index (DCUI) to facilitate the assessment of oral health interventions in the cost-utility analysis (CUA). This paper reports the protocol for a valuation study, which aims to generate a preference-based algorithm for the classification system for the DCUI. Methods and analysis: Discrete choice experiments (DCEs) will be conducted to value health states generated by the DCUI classification system and preferences for these health states will be modelled to develop a utility algorithm. DCEs produce utility values on a latent scale and these values will be anchored into the full health-dead scale to calculate the quality-adjusted life years in CUA. There is no previous evidence for the most suitable anchoring method for dental caries health state valuation. Hence, we will first conduct pilot studies with two anchoring approaches; DCE including duration attribute and DCE anchoring to worst heath state in Visual Analogue Scale. Based on the pilot studies, the most suitable anchoring method among two approaches will be used in the main valuation survey, which will be conducted as an online survey among a representative sample of 2000 adults from the Australian general population. Participants will be asked to complete a set of DCE choice tasks along with anchoring tasks, basic social-demographic questions, DCUI, a generic preference-based measure and oral health quality of life instrument. Ethics and dissemination: Ethical approval for this study was obtained from the Human Research Ethics Committee, Griffith University (reference number HREC/2019/550). The generated algorithm will facilitate the use of the new dental caries preference-based measure in economic evaluations of oral health interventions. The results will be disseminated through journal articles and professional conferences.